The Effect of Live Streaming Shopping on Purchase Intentions of Electronic Goods Through E-Commerce - Erlangga, Bayu; Imawan, Fathan Zidni; Atmaja Halim, Ferianie Herera; Kembaren, Julbintor (Journal Research of Social Science, Economics, and Management, 2025)
The rapid development of digital technology and social media has encouraged the increasing use of live streaming shopping features on e-commerce platforms in Indonesia. This phenomenon presents a new marketing communication pattern that allows direct interaction between streamers and consumers, especially in the category of electronic goods which is the sector with the highest e-commerce transaction value. This study aims to analyze the influence of live streaming shopping on consumer purchase intent using the Stimulus–Organism–Response (S-O-R) method. The stimulus variables tested included live streamer interaction, product quality, and e-commerce promotion; The organism variables include customer trust and impulsiveness, while the response variable is purchase intention. The research was carried out by method through the distribution of questionnaires that have witnessed live streaming shopping e-commerce in the past month and are in the Jakarta, Bogor, Depok, Tangerang, Bekasi area. The data was analyzed using PLS-SEM. The results of the study showed that product quality, e-commerce promotion, customer trust, and impulsiveness have a significant influence on purchase intent. In contrast, live streamer interaction had no significant effect on customer trust or impulsiveness, indicating that consumers of electronic goods considered functional aspects such as quality and promotion more than interpersonal interactions with streamers. Additionally, impulsiveness emerged as the most dominant factor in increasing buying intent. These findings strengthen the relevance of S-O-R theory in the context of live streaming shopping while providing practical implications for e-commerce players to improve credibility, information quality, promotional strategies, and impulsive trigger elements to encourage consumer purchase decisions.